Intuition in clinical decision-making by the nurse in ICU - Eben Arries; Annatjie Botes; Elsabe Nel (AOSIS, 2001)
This research article follows on a previous article where the results of a concept analysis of intuition were reported. Opsomming Hierdie artikel volg op 'n vorige een waarin die resultate van 'n konsepanalise van intuïsie beskryf is. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.